Unsettling sight: Judith Wright's journey into history and ecology on Mt Tamborine. Issue 2 (16th December 2015) - Cooke, Stuart
Abstract: Mt Tamborine is a crucial location for Judith Wright's poetry, and for the development of her thought. She wrote the majority of her poetry collections while living on the mountain from 1948–75; it was there that she came face to face with the complexities of Australian ecologies and colonial histories. While her earlier poems from this period reflect a concerted, anti-colonial desire to separate the world of Tamborine from her European inheritance and perspective, by the early 1970s her work becomes preoccupied with symbiotic relationships between her body, her house and garden, and the surrounding landscape. This turn reflects broader shifts in thought in the mid-twentieth century, where notions of separation and precision were being problematised by the emerging field of quantum mechanics.